Road Kill of Snakes on a Highway in an Orinoco Ecosystem: Landscape Factors and Species Traits Related to Their Mortality. (March 2019) - Rincón-Aranguri, Monica; Urbina-Cardona, Nicolás; Galeano, Sandra P.; Bock, Brian C.; Páez, Vivian P.
We sampled the snake fauna in 13 landscapes along 80 km of highway and in the adjacent vegetation cover in the Colombian Llanos. We registered 119 snakes belonging to 33 species. Traffic levels significantly influenced rates of snake road kill, while adjacent vegetation cover, rainfall seasonality, and landscape structure and composition did not. We classified the species into seven ecological groups based upon foraging strategy, body length, and habitat preferences. Although most of the road-killed species had an active foraging strategy, all of the ecological groups contained some species that were killed on the highway, as well as some species that inhabited adjacent vegetation cover but that were not detected on the highway. The different ecological groups were not associated with different landscape characteristics. Six of the 13 landscapes that presented the lowest species richness of road-killed species had a different ecological group represented by each of the species documented as road kills. Thus, considering the ecological group that a species belongs to provides a complementary analytical approach that permits a fuller understanding of the ecological effects of roads on the functional role of the species in the ecosystem. We recommend focusing mitigation measures on highway sectors with the greater vehicular flow, employing both preventive measures such as posting driver advisories and installing speed radars and conducting environmental education programs to raise awareness of local drivers.